(untitled) (Innovation in Woodworking Industry and Engineering design, 2026)
Last decades wood is promoted as building material. Unprotected wood exposed to outdoor conditions undergoes a variety of degradation induced essentially by fungi attacks. Heat treatment of wood by mild pyrolysis (180°C<T<240°C under inert atmosphere) is a preservation process with a weak environmental impact, and therefore, is viewed as an interesting alternative to the chemical impregnation methods. Nowadays, the main difficulties of industrial processes are to obtain final products with a constant quality (durability, dimensional stability, mechanical properties and colour). These difficulties may be due to the heat transfer or the inter-specific or intra-specific wood heterogeneity. The aim of this study is to better understand the effect of the intrinsic wood properties: density according to the position in wood, and especially early wood versus latewood, on the thermo-degradation process. Heat treatment using thermo-gravimetric analysis (TGA) was performed on small samples of the European oak (Quercus petraea Liebl.), where the earlywood and the latewood constituting the annual rings were studied separately. The relationship between the radial variation of wood density components assessed by microdensitometer and their thermo-degradation sensibility was investigated. The results show that globally, earlywood and latewood behaved differently under thermal conditions, for the two studied trees; earlywood tended to be more sensitive to thermo-degradation than latewood.